Patients With Short PFS to EGFR-TKIs Predicted Better Response to Subsequent Anti-PD-1/PD-L1 Based Immunotherapy in EGFR Common Mutation NSCLC - Liu, Sangtian; Wu, Fengying; Li, Xuefei; Zhao, Chao; Jia, Yijun; Jia, Keyi; Han, Ruoshuang; Qiao, Meng; Li, Wei; Yu, Jia; Zhou, Fei; Xiong, Anwen; et al. (Frontiers in Oncology, 2021)
Background Despite disappointing outcomes from monotherapy, studies reported that NSCLC patients with EGFR mutation may possibly benefit from combined immunotherapy. Whether the response to prior EGFR-TKI has association with the outcomes of subsequent immunotherapy remains unclear. Patients and Methods Advanced NSCLC patients with resistance to EGFR-TKIs and received ICI treatment from January 2016 to June 2019 were retrospectively analyzed. Single cell sequencing and flow cytometry were conducted to explore the difference of cell components in tumor microenvironments (TME). A 1:3 matched case-control study was conducted to compare the clinical effects of combined immunotherapy with standard chemotherapy as second-line treatment. Results Fifty-eight patients treated with anti-PD-1/PD-L1 based immunotherapy behind EGFR-TKI treatment were enrolled. Correlation analysis showed TKI-PFS had a significantly negative association with corresponding IO-PFS (r = -0.35, p = 0.006). TKI-PFS cutoff 10 months had the most significant predictive function for posterior immunotherapy and was validated to be an independent predictor by uni- and multivariate analysis. Kaplan-Meier analysis showed that patients with TKI-PFS less than 10 months had significantly prolonged IO-PFS and higher ORR than those with long (median PFS,15.1 vs 3.8 months; HR, 0.26, p=0.0002; ORR, 31.8% versus 10%, p=0.04). Single cell RNA-seq revealed that the cell components were varied among patients after treatment with EGFR-TKI. Patients with short TKI-PFS demonstrated a relatively higher proportion of CD8 effector cells and lower ratio of M2 like macrophage to M1 like macrophages, which was validated by flow cytometry. Case-control study demonstrated that combined immunotherapy achieved significantly longer PFS (HR, 0.51, 95% CI: 0.31-0.85, p=0.02), longer OS (HR, 0.48, 95% CI: 0.26-0.89, p=0.05) and higher ORR (33.3% vs 10.0%, p=0.02) than traditional chemotherapy for patients with short TKI-PFS. Conclusion Patients with short TKI-PFS conferred better response to immunotherapy than those with long. The status of TME were different among those two populations. Combined ICI treatment could promisingly be a better choice than classical chemotherapy in second-line setting for patients with short TKI-PFS and no T790M mutation. Underlying mechanisms need to be further explored.